GENOMIC ABERRATIONS IN DNA OF AFRICAN SWINE FEVER VIRUS CIRCULATING IN THE TERRITORY OF THE RUSSIAN FEDERATION - A. A. Varentsova; A. A. Yelsukova; N. G. Zinyakov; A. S. Igolkin; N. N. Vlasova (Ветеринария сегодня)
The paper is devoted to analysis of genome variability of African swine fever (ASF) virus isolates recovered in the Russian Federation territory. Complete nucleotide sequences of the following ASF virus isolate genomes were obtained by pyrosequencing: Kashino 04/13, Odintsovo 02/14 and Karamzino 02/13. Multiple single insertions and deletions as well as distinctly localized two tandem repeats were found by comparative analysis of genomes of the said isolates and Georgia 2007/1 isolate. Notably that 17-nucleotide tandem repeat was detected in 9R/10R intergenic region of MGF505 multigene family in genomes of Shikhobalovo 10/13 and Karamzino 02/13 isolates for the first time.